La prise en compte des dynamiques paysagères dans la construction d’indicateurs de bien-être destinés à l’évaluation des politiques publiques - Laurent Dalmas; Tristan Amiri; Jessy Tsang King Sang; Jean-François Noël (Développement Durable et Territoires)
Sectoral and land use public policies have to be assessed by indicators, particularly for their consequences on the population wellbeing. Considering that the landscape transformations are mainly due to socioeconomic activities, often guided by these policies, indicators cannot be based on the sole creation of wealth but have to integrate some considerations from landscapes dynamics. Land use data could help to characterize these dynamics in building new wellbeing composite indicators. They could be used to assess the « territorial governance » and the degree of social acceptability of these policies.